Cues for Better Writing: Empirical Assessment of a Word Counter and Cueing Application's Effectiveness. (December 2015) - Vijayasarathy, Leo R.; Gould, Susan Martin; Gould, Michael
Written clarity and conciseness are desired by employers and emphasized in business communication courses. We developed and tested the efficacy of a cueing tool—Scribe Bene—to help students reduce their use of imprecise and ambiguous words and wordy phrases. Effectiveness was measured by comparing cue word usage between a treatment group given the tool and a control group without the tool. In written assignments, the treatment group used 16 of 23 cue words significantly less than the control group and this effect persisted over time. Implications for using automated cueing tools in teaching written communication skills are discussed.